Diferensiasi Pendapat 4 Madzhab dengan Peraturan Kompilasi Hukum Islam Pasal 115 Tentang Hukum Jatuhnya Talak di Indonesia - Ainul Yaqin; Wakid Efendi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Differences in the legal validity of divorce (talak) between classical Islamic jurisprudence and Indonesian positive law continue to generate normative tension within Muslim society. The four major schools of Islamic law generally recognize the validity of talak when its essential elements are fulfilled, even if pronounced outside a court. In contrast, the Compilation of Islamic Law (KHI) requires that divorce be declared before a Religious Court to obtain legal recognition. This article examines the divergence between these two legal frameworks through a normative-comparative approach based on literature analysis of classical fiqh texts, statutory regulations, and contemporary scholarly works. The analysis highlights that classical jurisprudence prioritizes the formal validity of pronouncement, while KHI emphasizes legal certainty, procedural accountability, and protection of rights, particularly for women and children. The institutionalization of divorce through judicial mechanisms reflects a contextual legal adaptation intended to prevent misuse of unilateral authority and to ensure fairness in modern society. These findings indicate that although differing in procedural requirements, both frameworks share a common objective of safeguarding justice and public welfare. The Indonesian legal model demonstrates a form of contemporary ijtihad that integrates normative religious principles with socio-legal realities, making it more applicable within the current context.